Study of hyperpolarised 3He MRI diffusion on asthma and cystic fibrosis, and development of hyperpolarised 129Xe MRI lung imaging - Hardy, Steven M. (2016)
Hyperpolarised gas Magnetic Resonance Imaging (MRI) is a non-invasive method developed to provide images of the void spaces of the lungs, and evaluate the distal airways via diffusion weighted techniques. The work in this thesis covers the use of both hyperpolarised 3He and hyperpolarised 129Xe gas MRI, for both diffusion measurement studies and ventilation imaging, on healthy, asthmatic and cystic fibrosis volunteers. The first study covered in this thesis aimed to determine the nature of the acinar airway involvement in asthma sufferers via the use of Computed Tomography densitometry and hyperpolarised 3He diffusion MRI at multiple timescales alongside standard lung function tests such as spirometry and multiple breath washout (MBW). It was hypothesised that Asthma patients with an elevated MBW parameter 'Sacin' would manifest altered long-range diffusion, as suggestive of intra-acinar airway disease. It was found that there appeared to be an association between the MBW 'Sacin' parameter and subtle alterations in diffusion within the acinar airways for participants with asthma, suggesting a structural abnormality in the pulmonary acinus. However, further longitudinal studies are required before the long-term prognostic significance of acinar airway disease in asthma can be determined. The second study aimed to determine if a relationship exists between measurements from standard lung function test, spirometry and body plethysmography, and the measurements of hyperpolarised 3He diffusion MRI. 18 Cystic Fibrosis patients were recruited, alongside 27 age-matched healthy subjects. It was found that the short timescale diffusion values were lower in patients with Cystic Fibrosis, although not substantial enough to use an indicator to distinguish between a healthy volunteer and a Cystic Fibrosis patient. No strong correlations were found between the lung function measurements and the hyperpolarised 3He diffusion MRI measurements. The final section of this thesis looks at the preliminary results of a pilot study to develop scan sequences, protocols and gas delivery of hyperpolarised 129Xe MRI, in preparation for future clinical studies at the University of Nottingham. The main focus was on the development of in vivo ventilation images of the human lungs, to a high standard of quality and repeatability. Good progress was demonstrated, with lung images achieved down to 2.5 cm thick slices, with initial images of both dynamic ventilation and dissolved-phase 129Xe lung images. However the pilot study was not yet complete, and more development on the techniques discussed was still required.